Higher Cytokine and Opsonizing Antibody Production Induced by Bovine Serum Albumin (BSA)-Conjugated Tetrasaccharide Related to Streptococcus pneumoniae Type 3 Capsular Polysaccharide - Kurbatova, Ekaterina A.; Akhmatova, Nelli K.; Zaytsev, Anton E.; Akhmatova, Elina A.; Egorova, Nadezhda B.; Yastrebova, Natalya E.; Sukhova, Elena V.; Yashunsky, Dmitriy V.; Tsvetkov, Yury E.; Nifantiev, Nikolay E. (Frontiers in Immunology, 2020)
A number of studies have demonstrated the limited efficacy of S. pneumoniae type 3 capsular polysaccharide (CP) in the 13-valent pneumococcal conjugate vaccine against serotype 3 invasive pneumococcal diseases and carriage. Synthetic oligosaccharides (OSs) may provide an alternative to CPs for development of novel conjugated pneumococcal vaccines and diagnostic test systems. A comparative immunological study of di-, tri-, and tetra-BSA conjugates was performed. All oligosaccharides conjugated with biotin and immobilized on streptavidin-coated plates stimulated production of IL-1α, IL-2, IL-4, IL-5, IL-10, IFNγ, IL-17A, and TNFα, but not IL-6 and GM-CSF in monocultured mice splenocytes. The tetrasaccharide-biotin conjugate stimulated the highest levels of IL-4, IL-5, IL-10, and IFNγ, which regulate expression of specific immunoglobulin isotypes. The tetra-BSA conjugate adjuvanted with aluminum hydroxide elicited high levels of IgM, IgG1, IgG2a, and IgG2b antibodies (Abs). Anti-CP-induced Abs could only be measured using the biotinylated tetrasaccharide. The tetrasaccharide ligand possessed the highest binding capacity for anti-OS and antibacterial IgG Abs in immune sera. Sera to the tetra-BSA conjugate promoted greater phagocytosis of bacteria by neutrophils and monocytes than the CRM197-CP-antisera. Sera of mice immunized with the tetra-BSA conjugate exhibited the highest titer of anti-CP IgG1 Abs compared with sera of mice inoculated with the same doses of di- and tri-BSA conjugates. Upon intraperitoneal challenge with lethal doses of S. pneumoniae type 3, the tri- and tetra–BSA conjugates protected mice more significantly than the di-BSA conjugate. Therefore, it may be concluded that the tetrasaccharide ligand is an optimal candidate for development of a semi-synthetic vaccine against S. pneumoniae type 3 and diagnostic test systems